Giant Sublingual Dermoid Cyst in Floor of the Mouth - Jain, Harsha (Springer-Verlag, 2011)
The dermoid cysts of the mouth are most frequently located on the median line of the mouth floor and are most likely caused by the retention of the germinal epithelium during the growth of the mandible and hyoid branchial arches. We report an unusual case of giant dermoid cyst of the floor of the mouth in a 17-year female who presented with progressively increasing swelling below her tongue and reviewed the relevant literature.